Molecular phylogeny reveals high diversity, geographic structure and limited ranges in neotenic net-winged beetles platerodrilus (coleoptera: lycidae) - Masek, Michal; Palata, Vaclav; Bray, Timothy C; Bocak, Ladislav (PloS one, 2014)
The neotenic Platerodrilus net-winged beetles have strongly modified development where females do not pupate and retain larval morphology when sexually mature. As a result, dispersal propensity of females is extremely low and the lineage can be used for reconstruction of ancient dispersal and vicariance patterns and identification of centres of diversity. We identified three deep lineages in Platerodrilus occurring predominantly in (1) Borneo and the Philippines, (2) continental Asia, and (3) Sumatra, the Malay Peninsula and Java. We document limited ranges of all species of Platerodrilus and complete species level turnover between the Sunda Islands and even between individual mountain regions in Sumatra. Few dispersal events were recovered among the major geographical regions despite long evolutionary history of occurrence; all of them were dated at the early phase of Platerodrilus diversification up to the end of Miocene and no exchange of island faunas was identified during the Pliocene and Pleistocene despite the frequently exposed Sunda Shelf as sea levels fluctuated with each glacial cycle. We observed high diversity in the regions with persisting humid tropical forests during cool periods. The origins of multiple species were inferred in Sumatra soon after the island emerged and the mountain range uplifted 15 million years ago with the speciation rate lower since then. We suppose that the extremely low dispersal propensity makes Platerodrilus a valuable indicator of uninterrupted persistence of rainforests over a long time span. Additionally, if the diversity of these neotenic lineages is to be protected, a high dense system of protected areas would be necessary.
Keywords: Evolution, Molecular; molekulární evoluce; brouci; Sequence Analysis, DNA; fylogeografie; sekvenční analýza DNA; Animals; Phylogeography; Phylogeny; zvířata; fylogeneze; Coleoptera